The Jills : a novel [large type] - Parkman, Karen (Random House Large Print, 2026)
"Virginia is a Jill--a professional Buffalo Bills cheerleader--living the life she's always dreamed of. She spends her weekdays practicing, her weekends cheering, and her nights hopping between events and bars and clubs with her close-knit band of teammates, especially her best friend, Jeanine, whose dynamic friendship has given Virginia confidence in spades and allowed her to put aside her troubled past with her sister, Laura. But one Sunday, Jeanine fails to show up for a game, and all her calls and texts go unanswered. Aided by a worried network of Jills, ex-boyfriends, and seedy fixtures of Buffalo's criminal underground, Virginia embarks on an investigation into Jeanine's disappearance. But as her search grows increasingly dangerous and spirals into obsession, disturbing questions about who Jeanine really is begin to emerge. Soon, Virginia finds herself wondering how well she knows her friend, if she can trust the people and institutions she thought were protecting her, and whether--when trying to save the people she cares about most--she's capable of saving herself, too"--